AYYAKALI’S STRUGGLE FOR SOCIAL JUSTICE, SELF RESPECT AND UPWORD MOBILITY - P. Ramalakshmi; M, Sutha.; Femila, T.A. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Ayyankali (1863 – 1941) was the most influential anti – social leader in Trivancore. He had the courage to physically challenge the upper caste in order to achieve the rights of his pulaya people. He established sadhu Jana Paripalana Sangham (Association for the protection of the Poor – SJPS) in 1904.